Soft Mesoporous Organosilica Nanoplatforms Improve Blood Circulation, Tumor Accumulation/Penetration, and Photodynamic Efficacy - Peng, Xin; Chen, Kun; Liu, Wanhua; Cao, Xiongfeng; Wang, Mengru; Tao, Jun; Tian, Ying; Bao, Lei; Lu, Guangming; Teng, Zhaogang (Nano-Micro Letters, 2020)
To date, the ability of nanoplatforms to achieve excellent therapeutic responses is hindered by short blood circulation and limited tumor accumulation/penetration. Herein, a soft mesoporous organosilica nanoplatform modified with hyaluronic acid and cyanine 5.5 are prepared, denoted SMONs-HA-Cy5.5, and comparative studies between SMONs-HA-Cy5.5 (24.2 MPa) and stiff counterparts (79.2 MPa) are conducted. Results indicate that, apart from exhibiting a twofold increase in tumor cellular uptake, the soft nanoplatforms also display a remarkable pharmacokinetic advantage, resulting in considerably improved tumor accumulation. Moreover, SMONs-HA-Cy5.5 exhibits a significantly higher tumor penetration, achieving 30-μm deeper tissue permeability in multicellular spheroids relative to the stiff counterparts. Results further reveal that the soft nanoplatforms have an easier extravasation from the tumor vessels, diffuse farther in the dense extracellular matrix, and reach deeper tumor tissues compared to the stiff ones. Specifically, the soft nanoplatforms generate a 16-fold improvement (43 vs. 2.72 μm) in diffusion distance in tumor parenchyma. Based on the significantly improved blood circulation and tumor accumulation/penetration, a soft therapeutic nanoplatform is constructed by loading photosensitizer chlorin e6 in SMONs-HA-Cy5.5. The resulting nanoplatform exhibits considerably higher therapeutic efficacy on tumors compared to the stiff ones. Highlights: 1 Soft mesoporous organosilica nanoplatforms modified with hyaluronic acid and cyanine 5.5 are constructed. 2 Therapeutic efficacy of the soft nanoplatforms on tumor is higher both in vitro and in vivo after loading photosensitizer chlorin e6 compared to that of stiff counterparts.